Cannabidiol and Neurodevelopmental Disorders in Children - Kwan Cheung, Keith A.; Mitchell, Murray D.; Heussler, Helen S. (Frontiers in Psychiatry, 2021)
Neurodevelopmental and neuropsychiatric disorders (such as autism spectrum disorder) have broad health implications for children, with no definitive cure for the vast majority of them. However, in recent years, medicinal cannabis has been successfully trialled as an effective treatment to manage many of the patients’ symptoms and improve their quality of life. The cannabinoid cannabidiol, in particular, has been reported to be safe, well-tolerated with a plethora of anticonvulsant, anxiolytic and anti-inflammatory properties. Lately, the current consensus is that the endocannabinoid system is a crucial factor in neural development and health; research has found evidence that there are a multitude of signaling pathways involving neurotransmitters and the endocannabinoid system by which cannabinoids could potentially exert their therapeutic effects. A better understanding of the cannabinoids’ mechanisms of action should lead to improved treatments for neurodevelopmental disorders.